2006
DOI: 10.1021/jf061309q
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of anti-Pefloxacin Antibody and Development of an Indirect Competitive Enzyme-Linked Immunosorbent Assay for Detection of Pefloxacin Residue in Chicken Liver

Abstract: Pefloxacin has been increasingly used in veterinary medicine to treat microbial infections. To avoid using a labor-intensive instrumental method to detect the residue of pefloxacin in food, a simple and convenient indirect competitive enzyme-linked immunosorbent assay method has been developed in this study. The antibody generated from immunogen cationized bovine serum albumin-pefloxacin showed high sensitivity toward pefloxacin with an IC50 value of 6.7 ppb in buffer and was suitable for a screening assay to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 23 publications
(30 reference statements)
1
56
0
Order By: Relevance
“…The immunogen CPFX-BSA and the coating antigen CPFX-OVA were both prepared by carbodiimide active ester method as per a previous paper (Lu et al, 2006). A total of 3.86 mg of CPFX, 20.64 mg of EDC, and 5.76 mg of NHS were added to 0.23 ml DMF in order.…”
Section: Preparation Of Immunogen Cpfx-bsa and Coating Antigen Cpfx-ovamentioning
confidence: 99%
See 2 more Smart Citations
“…The immunogen CPFX-BSA and the coating antigen CPFX-OVA were both prepared by carbodiimide active ester method as per a previous paper (Lu et al, 2006). A total of 3.86 mg of CPFX, 20.64 mg of EDC, and 5.76 mg of NHS were added to 0.23 ml DMF in order.…”
Section: Preparation Of Immunogen Cpfx-bsa and Coating Antigen Cpfx-ovamentioning
confidence: 99%
“…Therefore, more and more organizations have issued maximum residue levels (MRLs) and withdrawal criterion for FQs. According to different food resources and drugs, the MRLs of FQs are set in a range of 30-1500 μg/kg (Lu et al, 2006;Zhao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cross-reactivity studies were carried out with the electrochemical immunoassay by adding various competitors in concentrations from 0.01 to 1000 ng/ml (Lu et al, 2006). The results confirmed that the anti-GAT antibody was highly specific and showed little cross-reactivity with lomefloxacin, ciprofloxacin, or ofloxacin (Table 1).…”
Section: Sensitivity and Specificity Of The Testmentioning
confidence: 60%
“…Enzyme-linked immunosorbent assay (ELISA) has been extensively used for screening of veterinary drug residues including fluoroquinolones in food and animal tissues (e.g., muscle, kidney, liver, serum, milk, and egg) due to its sensitivity, specificity, rapidity, and simplicity [20][21][22]. Nevertheless, using ELISA for determination of fluoroquinolones and other pharmaceuticals in water samples has still been rarely reported [23].…”
Section: Introductionmentioning
confidence: 99%